Impact of β-Glucuronidase Mediated Hydrolysis on Haldol® Urinalysis. Issue 4 (28th December 2017) - Cummings, Oneka T; Strickland, Erin C; Enders, Jeffrey R; McIntire, Gregory
Abstract: Reports have suggested that patients with mental health disorders including major depressive disorder and schizophrenia have dramatically low adherence levels to prescribed medications. Patients on haloperidol (Haldol®) therapy, regardless of their disease, were found to have higher adherence levels—though still strikingly low. This work shows that high levels of the glucuronidated form of haloperidol are present in patient urine samples. Time-of-Flight (TOF) mass spectrometry experiments are consistent with both the presence of haloperidol glucuronide and that hydrolysis of haloperidol patient urine samples leads to significantly increased concentrations of free haloperidol. Urine samples collected from patients prescribed haloperidol were tested with and without hydrolysis revealing a significant increase in the number of patients testing positive when the samples were hydrolyzed before analysis. These data demonstrate that hydrolysis greatly improves the sensitivity and consistency of results for patients on haloperidol therapy resulting in positivity data that strongly correlates with the dosage form administered.